Dynamics of the epistemological images of statehood in new European philosophy - Vorobyova, Svetlana V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article reveals the categorical and conceptual features of the dynamics of epistemological images of statehood in the new European philosophy based on two intellectual coalitions. The first coalition (F. Bacon, R. Descartes, B. Spinoza) made it possible to reveal the ways of legitimising knowledge in the context of the duality of empirical and rational approaches, which, accordingly, do not allow going beyond the immanence of statehood, and regulate its theoretical comprehension through monotonous discrete principles. On the basis of the second coalition (R. Descartes, T. Hobbes, J. Locke, B. Spinoza), changes in the schemes of categorisation and conceptualisation of statehood are traced and disclosed, the need to distinguish between explicit (hidden) and superficial (deep) structures is substantiated. It has been substantiated that the cultural transfer of categorical and conceptual features into modern studies of statehood is possible only in the dynamics of their interconnections.
Keywords: epistemological images of statehood; new European philosophy; categorisation; conceptualisation; legitimation of statehood; pragmatics of statehood